2000
DOI: 10.1152/ajpheart.2000.278.4.h1030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-wk estrogen withdrawal or replacement on myocardial ischemic tolerance in rats

Abstract: Menopausal status is a risk factor for coronary artery disease death, but the mechanism underlying this association is uncertain. To test whether estrogen ameliorates the effects of acute myocardial ischemia in ways likely to translate into a mortality difference, we compared the response to brief (6-min) and prolonged (45-min) coronary occlusion in vivo in five groups (each n = 16) of rats: ovariectomized females; ovariectomized females after 6 wk 17beta-estradiol replacement; male rats supplemented with estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
4
16
1
1
Order By: Relevance
“…This is in agreement with a recent study by McNulty et al (2000), who showed that estrogen withdrawal by ovariectomy for a 6-to 8-week period did not increase the myocardial infarct size of the isolated rat heart compared with normal and estrogenreplaced rats. On the other hand, the present study has shown that myocardial infarct size of female rats was smaller in response to ␤-AR stimulation during ischemia than that in Ovx rats and estrogen replacement restored the ability of the Ovx rats to resist ischemic injury.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a recent study by McNulty et al (2000), who showed that estrogen withdrawal by ovariectomy for a 6-to 8-week period did not increase the myocardial infarct size of the isolated rat heart compared with normal and estrogenreplaced rats. On the other hand, the present study has shown that myocardial infarct size of female rats was smaller in response to ␤-AR stimulation during ischemia than that in Ovx rats and estrogen replacement restored the ability of the Ovx rats to resist ischemic injury.…”
Section: Discussionsupporting
confidence: 93%
“…Ovariectomy, 6 weeks prior to acute coronary occlusion in female rats, is associated with myocardial infarct size similar to intact animals [32] and this is in accordance with our findings. In mice, however, gonadectomy in females, 6 weeks earlier, induced larger myocardial infarctions compared to controls [33]; in the same study, gonadectomy cancelled the protection of preconditioning whereas we found that ovariectomy does not affect the effect of preconditioning.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our laboratory's previous studies (39,43), serum estrogen concentration in the E animals was approximately eight-to ninefold higher compared with both S and P animals and was at the high end of normal for rodents (23,39,52). The E animals were significantly lighter than both S and P animals, which is believed to be due to differences in insulin-like growth factor-1 and growth hormone release, which are downregulated by estrogen (7,39).…”
Section: Discussionsupporting
confidence: 88%